Da Idade do Ferro ao final do Império Romano no Centro Histórico de Oeiras: o contributo dos espólios recuperados nas escavações realizadas entre 2000 e 2007: DOI: https://doi.org/10.5281/zenodo.7920549 - Cardoso, João Luís; Cardoso, Guilherme; Batalha, Luísa; André, Maria da Conceição (Estudos Arqueológicos de Oeiras, 2023)
The archaeological remains attributable to the Iron Age, the Republican and the Imperial Roman periods, collected in the excavations carried out in the Historic Center of Oeiras between 2000 and 2007, in the place where in 1903 a Roman mosaic attributed to the 3rd/4th century AD was identified are studied. The remains, including amphorae, common productions and fine productions, and exceptionally, glasses, bone and metal implements, document the human presence of the successive populations that lived in the place currently occupied by the town of Oeiras over a period of about 500 years, contributing to the knowledge of its economy and social organization. Together with the results of other recently published interventions, this study is a contribution to the knowledge of the ancient occupation of this urban space during Roman times.